Memahami Makna Kesuksesan dalam Novel Alang: Hidup Tak Pernah Memberi Bahu untuk Bersandar Karya Desi Puspitasari - Ocha Wahyu Perdana; Suhartono Suhartono; Sarwit Sarwono (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2020)
A good novel has a meaning in life that is beneficial for its readers. For this reason, it is important to study the meaning of life, especially the meaning of success. The purpose of this study was to describe the meaning of life contained in the novel Alang: Hidup Tak Pernah Memberi Bahu untuk Bersandar by Desi Puspitasari. The research method uses the Hermeneutic Paul Riceour method. Data collection techniques using documentation techniques in the form of the novel Alang: Hidup Tak Pernah Memberi Bahu untuk Bersandar by Desi Puspitasari. Data validity test uses hermeneutic expert validation. The results show that the meaning in the novel Alang: Hidup Tak Pernah Memberi Bahu untuk Bersandar by Desi Pupitasari work is success that determines who we are, other factors such as family and friends have very little influence.